2014
DOI: 10.1057/bm.2014.7
|View full text |Cite
|
Sign up to set email alerts
|

From endorsement to celebrity co-branding: Personality transfer

Abstract: Laure Ambroiseis an assistant professor at University of Saint Etienne (France). Her studies focus on consumers and brands relationship. She has published articles in international refereed marketing journals and conferences, especially on brand management (Recherche et Applications en Marketing, Advances in Consumer Research). Her recent research projects cover brand personality transfer and consumer empowerment. Gaëlle Pantin-Sohieris an assistant professor at University of Angers (France). Her research expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 37 publications
(55 reference statements)
2
41
1
2
Order By: Relevance
“…This result contradicts conventional thinking that endorsements' effectiveness is enhanced with increasing repetitions (* Till et al 2008). Although endorsement effects have been found at single exposures (Ambroise et al 2014), advertisements are assumed to be learned more thoroughly when exposed multiple times (wearin), as long as consumers are not bored or annoyed by too much repetition (wearout; Campbell and Keller 2003). Wearout seems rather unlikely in this study, as the maximum number of exposures included in the specific analysis was five, and as Bfive pairings is not so many as to cause subject boredom but is likely to lead to conditioning effects^(* Till et al 2008).…”
Section: Discussion Main Findings and Contributionscontrasting
confidence: 65%
See 3 more Smart Citations
“…This result contradicts conventional thinking that endorsements' effectiveness is enhanced with increasing repetitions (* Till et al 2008). Although endorsement effects have been found at single exposures (Ambroise et al 2014), advertisements are assumed to be learned more thoroughly when exposed multiple times (wearin), as long as consumers are not bored or annoyed by too much repetition (wearout; Campbell and Keller 2003). Wearout seems rather unlikely in this study, as the maximum number of exposures included in the specific analysis was five, and as Bfive pairings is not so many as to cause subject boredom but is likely to lead to conditioning effects^(* Till et al 2008).…”
Section: Discussion Main Findings and Contributionscontrasting
confidence: 65%
“…Given that consumers already possess a rich network of associations representing an object, attitudes, and behavior appear more difficult to change (Cacioppo et al 1992). Accordingly, Ambroise et al (2014) reported stronger celebrity endorsement effects with unfamiliar compared to familiar brands. Similarly, Shimp et al (1991) showed the likelihood of conditioning effects for unknown or moderately known objects, but not for well-known ones.…”
Section: Moderatorsmentioning
confidence: 96%
See 2 more Smart Citations
“…This notion is further verified by the recently held empirical studies found in the scope of celebrity endorsement referring source-based and management-based factors as the content of effectiveness of celebrity endorsements ( Ambroise, Sohier, Florence & Albert ,2014;Fleck, Korchia & Roy,2012;Ibok & Ibok ,2013;Okyere & Asamoah 2015;Rachita, Nirmal & Priya,2013;Spry, Pappu & Cornwell,2011& Tzoumaka,et.al. 2014.…”
Section: Background Of the Study: Notion Of Effectiveness Of Celebritmentioning
confidence: 54%